Promoting inclusion in clinical trials—a rapid review of the literature and recommendations for action - Bodicoat, Danielle H.; Routen, Ash C.; Willis, Andrew; Ekezie, Winifred; Gillies, Clare; Lawson, Claire; Yates, Thomas; Zaccardi, Francesco; Davies, Melanie J.; Khunti, Kamlesh (Current controlled trials in cardiovascular medicine, 2021)
Background Without inclusion of diverse research participants, it is challenging to understand how study findings will translate into the real world. Despite this, a lack of inclusion of those from under-served groups in research is a prevailing problem due to multi-faceted barriers acting at multiple levels. Therefore, we rapidly reviewed international published literature, in relation to clinical trials, on barriers relating to inclusion, and evidence of approaches that are effective in overcoming these. Methods A rapid literature review was conducted searching PubMed for peer-reviewed articles that discussed barriers to inclusion or strategies to improve inclusion in clinical trial research published between 2010 and 2021. Grey literature articles were excluded. Results Seventy-two eligible articles were included. The main barriers identified were language and communication, lack of trust, access to trials, eligibility criteria, attitudes and beliefs, lack of knowledge around clinical trials, and logistical and practical issues. In relation to evidence-based strategies and enablers, two key themes arose: [ 1 ] a multi-faceted approach is essential [ 2 ]; no single strategy was universally effective either within or between trials. The key evidence-based strategies identified were cultural competency training, community partnerships, personalised approach, multilingual materials and staff, communication-specific strategies, increasing understanding and trust, and tackling logistical barriers. Conclusions Many of the barriers relating to inclusion are the same as those that impact trial design and healthcare delivery generally. However, the presentation of these barriers among different under-served groups may be unique to each population’s particular circumstances, background, and needs. Based on the literature, we make 15 recommendations that, if implemented, may help improve inclusion within clinical trials and clinical research more generally. The three main recommendations include improving cultural competency and sensitivity of all clinical trial staff through training and ongoing personal development, the need to establish a diverse community advisory panel for ongoing input into the research process, and increasing recruitment of staff from under-served groups. Implementation of these recommendations may help improve representation of under-served groups in clinical trials which would improve the external validity of associated findings.